PENGEMBANGAN MEDIA VISUAL KARTU ANGKA EFEKTIF UNTUK MENGENALKAN HURUF VOKAL A, I, U, E, O PADA ANAK USIA DINI 3-4 TAHUN PAUD LABSCHOOL JEMBER - Ratnasari Dwi Ade Chandra (Universitas Muhammadiyah Ponorogo, 2017)
This research to know the effectiveness of development visual media flashcard to introduce letters vocal in early childhood. Research carried out in Paud Labschool Jember using a purposive samplingtechnique, over media visual flashcard who participated in school learning activities. Data is taken from trial data product consists of the design validation, Individual Trial, Trial Small, Large Trial. The analysis method is using the normality analysis test and t-test. The trials test design used is the One Group Pre-Test type Experimental Design and Post-Test Design type. Results of normality data testbefore using flashcard visual media data showed that significant value Kolmogorov Smirnov is 0,014 and value significant of Shapiro-Wilk is 0,041. Normality test results indicate that significant value is greater than the minimum limit is sig ≥ 0.05 : meaning that the data obtained is a normal distribution. Data normality test results after using visual media flashcard data showed that the significant value of 0.063 Kolmogorov Smirnov and Shapiro-Wilk significant value of 0.06. Data normality test results after using visual media flashcard data showed that the significant value of 0.063 Kolmogorov Smirnov and Shapiro-Wilk significant value of 0.06. Normality test results indicate that significant value is greater than the minimum limit is ≤ 0.05 sig: meaning that the data obtained normal distribution. the results of paired samples t test, t test (t) of -9.255 and significance value (sig) of 0.000. Value t test (t) is greater than t table criteria that is -3.120. Significant value paired sample t-tes is smaller than the specified limit is 0.05 (sig 0.05). It can be concluded if there are significant differences on early childhood cognitive ability before and after visual media flashcard (Ha acceptable)